2022
DOI: 10.1038/s41598-022-15956-3
|View full text |Cite
|
Sign up to set email alerts
|

A multi-epitope vaccine designed against blood-stage of malaria: an immunoinformatic and structural approach

Abstract: Malaria is a complex disease caused by parasites of the genus Plasmodium and is the leading cause of morbidity and mortality worldwide. The most severe form of malaria disease is caused by Plasmodium falciparum. Thus, a combination of different approaches is needed to control malaria. Resistance to first-line drugs and insecticides, on the other hand, makes the need for an effective vaccination more urgent than ever. Because erythrocyte parasites cause the most clinical symptoms, developing a vaccination for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…In this study, like many other studies, the AAY linker was used to connect CTL epitopes [ 85 , 111 , 112 ], the GGGGS linker to connect HTL epitopes [ 113 , 114 ], the KK linker to connect LBL epitopes [ 115 117 ], and the EAAAK linker to connect adjuvant [ 116 , 118 , 119 ]. The AAY linkers help to increase epitope presentation while decreasing the formation of junctional epitopes [ 120 ]. The GGGGS linker, which is made up of small or polar amino acids like Gly and Ser, provides good flexibility and solubility and is an excellent choice for fusion protein domains that require specific movements or interactions [ 121 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, like many other studies, the AAY linker was used to connect CTL epitopes [ 85 , 111 , 112 ], the GGGGS linker to connect HTL epitopes [ 113 , 114 ], the KK linker to connect LBL epitopes [ 115 117 ], and the EAAAK linker to connect adjuvant [ 116 , 118 , 119 ]. The AAY linkers help to increase epitope presentation while decreasing the formation of junctional epitopes [ 120 ]. The GGGGS linker, which is made up of small or polar amino acids like Gly and Ser, provides good flexibility and solubility and is an excellent choice for fusion protein domains that require specific movements or interactions [ 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…The KK linker is a target for cathepsin B, a key protease in antigen processing. This linker helps in the reduction of junctional immunogenicity by preventing antibody induction for the peptide sequence formed when the individual epitopes are linearly connected [ 120 ]. The EAAAK linker is a rigid alpha-helix-forming peptide linker that functions as a domain spacer in fusion proteins [ 122 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both structures fluctuated, indicating their considerable flexibility and validating it as suitable vaccine structures. Similarly, Atapour et al [58] recorded a high degree of fluctuation in the residues at positions 219 and 617 in a P. falciparum multi-epitope vaccine. The results obtained in the form of B-factor and deformability plots indicated that the molecular structures of both of the peptides were stable, and the overall stability of the VT2 constructs was higher compared to the VT1.…”
Section: Discussionmentioning
confidence: 85%
“…A multi-epitope vaccine was designed against the blood stage of P. falciparum by selecting multiple epitopes of P. falciparum glutamic acid-rich protein (PfGARP) protein. A total of 10 epitopes (5 B and 5 HTL epitopes) were linked by suitable linkers along with flagellin adjuvant to enhance the immunogenicity of the vaccine construct (169). While in silico immune simulation resulted in an elevated humoral and cellular immune response against malaria, such in silico studies need further in vitro and in vivo evaluations (169).…”
Section: Current Vaccine Approachesmentioning
confidence: 99%
“…A multi-epitope vaccine was designed against the blood stage of P. falciparum by selecting multiple epitopes of P. falciparum glutamic acid-rich protein ( Pf GARP) protein. A total of 10 epitopes (5 B and 5 HTL epitopes) were linked by suitable linkers along with flagellin adjuvant to enhance the immunogenicity of the vaccine construct ( 169 ). While in silico immune simulation resulted in an elevated humoral and cellular immune response against malaria, such in silico studies need further in vitro and in vivo evaluations ( 169 ).…”
Section: Vaccine Candidates Against Plasmodiummentioning
confidence: 99%